Cost-effectiveness of a multifaceted podiatry intervention for the prevention of falls in older people: the reducing falls with orthoses and a multifaceted podiatry intervention trial findings - Corbacho, B; Cockayne, S; Fairhurst, C; Hewitt, C; Hicks, K; Kenan, A; Lamb, S; MacIntosh, C; Menz, H; Redmond, A; Rodgers, S; Scantlebury, A; et al. (Karger Publishers, 2018)
Background: Falls are a major cause of morbidity among older people. Multifaceted interventions may be effective in preventing falls and related fractures. Objective: To evaluate the cost-effectiveness alongside the REducing Falls with Orthoses and a Multifaceted podiatry intervention (REFORM) trial. Methods: REFORM was a pragmatic multicentre cohort randomised controlled trial in England and Ireland; 1,010 participants (> 65 years) were randomised to receive either a podiatry intervention (n = 493), including foot and ankle strengthening exercises, foot orthoses, new footwear if required, and a falls prevention leaflet, or usual podiatry treatment plus a falls prevention leaflet (n = 517). Primary outcome: incidence of falls per participant in the 12 months following randomisation. Secondary outcomes: proportion of fallers and quality of life (EQ-5D-3L) which was converted into quality-adjusted life years (QALYs) for each participant. Differences in mean costs and QALYs at 12 months were used to assess the cost-effectiveness of the intervention relative to usual care. Cost-effectiveness analyses were conducted in accordance with National Institute for Health and Clinical Excellence reference case standards, using a regression-based approach with costs expressed in GBP (2015 price). The base case analysis used an intention-to-treat approach on the imputed data set using multiple imputation. Results: There was a small, non-statistically significant reduction in the incidence rate of falls in the intervention group (adjusted incidence rate ratio 0.88, 95% CI 0.73–1.05, p = 0.16). Participants allocated to the intervention group accumulated on average marginally higher QALYs than the usual care participants (mean difference 0.0129, 95% CI –0.0050 to 0.0314). The intervention costs were on average GBP 252 more per participant compared to the usual care participants (95% CI GBP –69 to GBP 589). Incremental cost-effectiveness ratios ranged between GBP 19,494 and GBP 20,593 per QALY gained, below the conventional National Health Service cost-effectiveness thresholds of GBP 20,000 to GBP 30,000 per additional QALY. The probability that the podiatry intervention is cost-effective at a threshold of GBP 30,000 per QALY gained was 0.65. The results were robust to sensitivity analyses. Conclusion: The benefits of the intervention justified the moderate cost. The intervention could be a cost-effective option for falls prevention when compared with usual care in the UK.